Factors affecting goods and services tax (GST) compliance among small medium enterprise (SME) in Malaysia / Soliha Sanusi - Sanusi, Soliha (2019)
Goods and Services Tax (GST) plays a significant role during these three-year periods (2016 to 2018) as Malaysia’s main source of income of crude oil suffered from the worldwide downward price trends along with the weakened Ringgit Malaysia (RM). Small-medium enterprises, the biggest numbers of the GST registrants were acknowledged for their contribution to the Malaysian economy despite its capital constraint. However, the sole agency in charge of GST compliance, the Royal Malaysian Customs Department (RMC) argued that there are a high number of noncompliance cases involving small and medium enterprises during the GST’s initial implementation periods of 2015 to 2017. Therefore, the main aim of this research is to provide empirical evidence on factors that affect the GST compliance among small and medium enterprises in Malaysia. In this study, the operational definition of compliance has been refined to include three main processes, i.e. submitting tax return whenever required; disclosing all taxable income and settling the assessed tax by the due dates. Four research objectives with ten hypotheses were generated for the study. A mixed method of quantitative questionnaire surveys, and qualitative face-to-face and focus group interviews were used to collect data for the study. The questionnaire survey study was administered to sample GST registrants from among small and medium enterprises. A total of 379 owners/top management of small and medium enterprise participated in the study. This quantitative study was conducted to examine the relationship between voluntarism and enforcement factors on GST compliance behaviours. Structural analysis of Smart PLS was performed on both voluntarism and enforcement factors to determine which elements that would be a stronger determinant of taxpayers’ compliance behaviour.